ASSESSMENT OF NATURAL GROUNDWATER RESOURCES OF ARMENIA ACCORDING TO THE LAW OF RA “NATIONAL WATER PROGRAM” (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The article deals with the evaluation of individual components of natural groundwater resources in the framework of the "National Water Program" of the Republic of Armenia. In particular, the law employs terms such as "used ground water resources", "strategic and national reserves of groundwater". There are no such terms in hydrogeological literature, and their statements are missing in the law and there are no methods of evaluating them that are important for rational management of groundwater resources of Armenia. The article provides formulation and methods for assessing these terms with reference to specific watersheds of the rivers of RA.
Keywords: usable water resources; strategic and national reserves; renewable groundwater resource; groundwater flow; dry flow